2017
DOI: 10.1002/ece3.3311
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary divergence in life history traits among populations of the Lake Malawi cichlid fishAstatotilapia calliptera

Abstract: During the early stages of adaptive radiation, populations diverge in life history traits such as egg size and growth rates, in addition to eco‐morphological and behavioral characteristics. However, there are few studies of life history divergence within ongoing adaptive radiations. Here, we studied Astatotilapia calliptera, a maternal mouthbrooding cichlid fish within the Lake Malawi haplochromine radiation. This species occupies a rich diversity of habitats, including the main body of Lake Malawi, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Nonetheless, we observed transmission of mutations to the next generation in both cases. A. calliptera species reach maturity on average at 8 months at which point they usually lay on average ~20 eggs, with clutch size increasing with age and size (Parsons et al, 2017). Despite low survival and low clutch sizes at young ages, germline transmission is high and as such it is possible to establish a breeding population of stable mutant A. calliptera within 16 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, we observed transmission of mutations to the next generation in both cases. A. calliptera species reach maturity on average at 8 months at which point they usually lay on average ~20 eggs, with clutch size increasing with age and size (Parsons et al, 2017). Despite low survival and low clutch sizes at young ages, germline transmission is high and as such it is possible to establish a breeding population of stable mutant A. calliptera within 16 months.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report the application of CRISPR/Cas9 to generate coding and non-coding sequence mutants in the cichlid Astatotilapia calliptera, a maternal mouthbrooder cichlid fish that is part of the Malawi haplochromine radiation. A. calliptera occupies a rich diversity of habitats, including Lake Malawi, as well as peripheral rivers and lakes (Parsons et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Collections at the type locality: Astatotilapia calliptera is well-known from many recent studies (e.g. Konings 2016;Nichols et al 2015;Parsons et al 2017;Peterson et al 2017;Tyers & Turner 2013) and appears to be more or less ubiquitous in shallow weedy areas in Lake Malawi and its catchment. A striking population with blue-grey adult males is reported from Chizumulu Island (Konings 2016), but other populations seem phenotypically quite similar, with males showing a spectacular multi-colouredlargely golden yellow -breeding dress (Figure 54-58).…”
Section: Astatotilapia Calliptera (Günther 1894)mentioning
confidence: 99%
“…egg size and fecundity, in mouthbrooding cichlids were shown to evolve in parallel to different habitats across the 3 radiations [ 40 ]. It was also recently reported that various life-history traits such as clutch size and egg mass in a riverine haplochromine, Astatotilapia burtoni , were diverging at the population level, suggestive of ‘ongoing’ adaptive radiation [ 41 ]. Furthermore, haplochromines have evolved numerous trophic adaptations to acquire different food sources such as algae, snails, insects and shrimp [ 42 ].…”
Section: Introductionmentioning
confidence: 99%